2017
DOI: 10.5194/acp-17-11623-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mercury in the Southern Hemisphere tropics: seasonal and diurnal variations and influence of inter-hemispheric transport

Abstract: Abstract. Mercury is a toxic element of serious concern for human and environmental health. Understanding its natural cycling in the environment is an important goal towards assessing its impacts and the effectiveness of mitigation strategies. Due to the unique chemical and physical properties of mercury, the atmosphere is the dominant transport pathway for this heavy metal, with the consequence that regions far removed from sources can be impacted. However, there exists a dearth of long-term monitoring of atm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 64 publications
5
34
1
Order By: Relevance
“…Similar nocturnal depletion events have been reported elsewhere (e.g. Engle et al, 2010;Peleg et al, 2015;Fu et al, 2016;Howard et al, 2017) and differ from the better-known polar AMDEs (Steffen et al, 2008, and reference within), as the former take place in the absence of sunlight and photolytic reactions. HYSPLIT trajectories showed no distinct source pattern for NAMDE nights, suggesting that the observed phenomena are due to local interactions and not the result of long-range transport of depleted air masses such as those observed by Gauchard et al (2005), Mastromonaco et al (2016) and Moore et al (2014).…”
Section: Nocturnal Atmospheric Mercury Depletion Eventssupporting
confidence: 48%
See 1 more Smart Citation
“…Similar nocturnal depletion events have been reported elsewhere (e.g. Engle et al, 2010;Peleg et al, 2015;Fu et al, 2016;Howard et al, 2017) and differ from the better-known polar AMDEs (Steffen et al, 2008, and reference within), as the former take place in the absence of sunlight and photolytic reactions. HYSPLIT trajectories showed no distinct source pattern for NAMDE nights, suggesting that the observed phenomena are due to local interactions and not the result of long-range transport of depleted air masses such as those observed by Gauchard et al (2005), Mastromonaco et al (2016) and Moore et al (2014).…”
Section: Nocturnal Atmospheric Mercury Depletion Eventssupporting
confidence: 48%
“…Wind direction and HYSPLIT analyses showed that there was no influence from significant GEM sources. These values are lower than annual mean sea-level measurements recently reported across the Southern Hemisphere (Slemr et al, 2015;Howard et al, 2017). Analysis of the systematic uncertainty of the 2537 system by Slemr et al (2015) suggests this can be on the order of 0.1 ng m −3 .…”
Section: Gem Concentrationsmentioning
confidence: 43%
“…ATARS also now serves as an additional site measuring continuous GEM as part of the Global Mercury Observation System (GMOS), one of only two tropical observing sites in the eastern hemisphere and the third such site located in Australia. A discussion of the seasonal and diurnal variations of atmospheric mercury at the ATARS site can be found in Howard et al (2017).…”
Section: Emission Factors and Gaseous Species Loadingsmentioning
confidence: 99%
“…Sulfate contributions were very significant during the coastal period, contributing up to 32 % of the total mass. Although chlorides contributed the least to the total mass on average, during clear biomass burning events where sharp increases in CO and organics were Wang et al (2017) Emissions of selected semivolatile organic chemicals from forest and savannah fires Milic et al (2017) Biomass burning and biogenic aerosols in northern Australia during the SAFIRED campaign Mallet et al (2017) Composition, size and cloud condensation nuclei activity of biomass burning aerosol from northern Australian savannah fires Desservattaz et al (2017) Emission factors of trace gases and particles from tropical savanna fires in Australia Howard et al (2017) Atmospheric mercury in the southern hemisphere tropics: seasonal and diurnal variations and influence of inter-hemispheric transport observed, chlorides made up the largest component of inorganic aerosol. Organic carbon made up approximately 80 to 90 % of the total carbon (organic carbon + elemental carbon) PM 1 mass during the campaign, with the exception of BBP3, when this dropped to 70 %.…”
Section: Fires and Air Massesmentioning
confidence: 99%
“…The wet and dry deposition (direct or uptake by sea-salt aerosol) represents a major input of RGM and Hg P to the sea and ocean due to their special and unique characteristics (i.e., high reactivity and water solubility) Holmes et al, 2009). Previous studies also showed that atmospheric wet and dry deposition of RGM (mainly HgBr 2 , HgCl 2 , HgO, Hg-nitrogen, and sulfur compounds) was the greatest source of Hg to open oceans (Holmes et al, 2009;Mason et al, 2012;Huang et al, 2017). A recent study suggested that approximately 80 % of atmospheric reactive Hg sinks into the global oceans, and most of the deposition takes place in the tropical oceans (Horowitz et al, 2017).…”
mentioning
confidence: 99%